(untitled) (Research, Society and Development, 2025)
In Brazil, the bakery sector plays a fundamental role in the economy, with micro and small businesses representing the majority of establishments. These businesses face challenges related to cost management and appropriate product pricing. In this context, the present study aims to demonstrate the application of the ABC Costing Method in a bakery, analyzing its efficiency in the strategic management of items with the greatest impact on costs and profitability. As a methodology, a literature review on the topic was conducted, complemented by a case study that enabled the practical application of the discussed concepts. The results showed that the ABC Method allowed the elimination of distortions caused by traditional costing, thereby increasing the effectiveness of the bakery’s financial management. It proves to be a modern cost management approach, essential for facing market challenges and maximizing the profitability of bakeries.